Insecure attachment styles as predictors of posttraumatic growth in a South African student sample. (March 2023) - Schuitmaker, Nicole; Basson, Pieter; Kruger, Gert
South Africa, as a developing country, is characterized by high levels of crime, partner violence, and other traumatic experiences. Exposure to these traumas may lead to the development of post-traumatic stress disorder or, conversely, post-traumatic growth. Citizens in developing African countries appear to be at risk for the development of insecure attachment styles due to the cumulative effects of socio-economic risk factors. The prevalence of many possible traumatic experiences along with the risk of more insecure attachments set the stage for investigating the impact of insecure attachment on post-traumatic growth. The aim of this study was thus to determine whether two insecure attachment styles, namely anxious and avoidant attachment, were significant predictors of post-traumatic growth. The sample consisted of 233 undergraduate students from a South African university who had experienced a traumatic event. Participants' ages ranged from 18 to 33 years ( M  = 21 years) and were from various ethnic backgrounds (81.5% Black African, 7.7% White, 9% Coloured, and 3.9% Asian/Indian). Two self-report measures were administered via an online survey to assess attachment styles and post-traumatic growth. Results showed that an anxious attachment style was a significant negative predictor of post-traumatic growth. Furthermore, individuals with an avoidant attachment style were significantly less likely to experience post-traumatic growth through relating to others, than along the other domains of post-traumatic growth. The findings contribute by highlighting the importance of considering how insecure attachment styles may impact post-traumatic growth, as this could inform the treatment of trauma victims.